The diversity of morphological characteristics and chemical content of Celosia cristata plantlets due to gamma ray irradiation - IZZATUL MUHALLILIN; SYARIFAH IIS AISYAH; DEWI SUKMA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Muhallilin I, Aisyah SI, Sukma D. 2019. The diversity of morphological characteristics and chemical content of Celosia cristata plantlets due to gamma ray irradiation. Biodiversitas 20: 862-866. Celosia cristata L. or better known as Jengger Ayam is an ornamental plant that has a unique flower shape with attractive colors. Besides, this plant also contains antioxidants and chemical compounds that are used for traditional medicine to treat high blood pressure, and diabetes or as eye ailments. Increased diversity of C. cristata through hybridization techniques is constrained by flowers forming small grains that makes it difficult for castration and isolation of reproductive organs. This study aimed to increase C. cristata diversity of morphology and chemical content using mutation techniques induced by gamma irradiation. Plantlets were irradiated at 0, 25, 50 and 75 Gy doses. Scoring was conducted for 5 weeks until MV6 generation. Planlets were acclimatized for 3 weeks. The surviving plants were moved onto experimental land until seeded and tested for phytochemicals. Gamma irradiation with 25, 50 and 75 Gy doses produced 4 clones that have morphological changes in color and shape of the stem, leaves, and flowers. Changes in chemical content were observed with the appearance of triterpenoid compounds in 1 clone irradiated with 25 Gy.